A Social Semiotic Analysis of Register Variables in the Indonesian Government-Distributed English Textbook - Elih Sutisna Yanto; Hikmah Pravitasari (English Learning Innovation (englie), 2022)
While the inclusion of Genre-Based Approach (GBA) as language pedagogy globally has received extensive attention in recent years, research on evaluating ELT textbooks focusing on the register representation remains relatively scarce. Drawing on the framework of social semiotic text analysis as the functional variety of language and register theory: field, mode and tenor, the present study aimed to explore Indonesian Ministry of Education and Culture-endorsed secondary school English textbook from the perspective of textbooks as “a resource for making meanings—language as a social semiotic.” The findings revealed that language textbooks should be viewed as sociocultural artifacts that feature register or the context of situation representation. This article examines the research question in what ways register variables are portrayed in one Indonesian Ministry of National Education-approved secondary school English textbook, which deploys various genres and discursive resources. This critical analysis reveals that verbal texts with different genres in the textbook represent a myriad of contexts of which both teachers and students need to become aware. The implication of this study suggests that both teachers and students need to equip with skills in analyzing and reading as well as in critical language awareness analysis. Both teachers and students should have the opportunity to engage critically with textbooks as a socio-semiotic agent, for instance.